Hippocrates: facts and fiction - Francois P. Retief; Louise Cilliers (Acta Theologica)
Hippocrates, the Father of Medicine, is reviewed as a historical person and in terms of his contribution to medicine in order to distinguish fact from fiction. Contemporary and later sources reveal that many (possibly untrue) legends accumulated around this enigmatic figure. The textual tradition and the composition of the socalled Corpus Hippocraticum, the collection of medical works written mainly in the 5th and 4th centuries BC (of which possibly only about five can be ascribed to Hippocrates himself) are discussed. The origin of the Hippocratic Oath, and the impact of the Hippocratic legacy on modern medicine are considered.